Chemical reaction effects on stretching/shrinking vertical surface in stagnation point flow - Ahmad Kardri, Mahani; Bachok @ Lati, Norfifah; Md Ali, Fadzilah; Md Arifin, Norihan (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The effects of chemical reaction on nanofluid vertical surface were considered on the flow of stagnation point. The numerical results were obtained by MATLAB to observe the impacts of the parameter of chemical reaction to the governing parameters. The results are graphically portrayed to observe the presence of dual solutions. The validation of the results is compared to the previous study and tends to give a favorable argument.